It is currently 15 Dec 2018, 03:05
My Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:
Senior Manager
Senior Manager
Joined: 20 May 2014
Posts: 282
Followers: 15

Kudos [?]: 49 [0], given: 220

CAT Tests
If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi [#permalink] New post 20 Nov 2017, 11:17
00:00

Question Stats:

81% (00:20) correct 18% (00:42) wrong based on 11 sessions
If 2x − 3y = 6, then 6y − 4x =

A. −12
B. −6
C. 6
D. 12
E. Cannot be determined

Kudos for correct solution.
[Reveal] Spoiler: OA
1 KUDOS received
Director
Director
Joined: 20 Apr 2016
Posts: 758
Followers: 6

Kudos [?]: 514 [1] , given: 94

CAT Tests
Re: If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi [#permalink] New post 01 Dec 2017, 21:44
1
This post received
KUDOS
Bunuel wrote:
If 2x − 3y = 6, then 6y − 4x =

A. −12
B. −6
C. 6
D. 12
E. Cannot be determined




Here we have,

2x − 3y = 6

or 2(2x − 3y) = 12 (multiplying by 2)

or 6y- 4x = -12 (multiplying by negative)

Hence option A
_________________

If you found this post useful, please let me know by pressing the Kudos Button

1 KUDOS received
Target Test Prep Representative
User avatar
Status: Head GRE Instructor
Affiliations: Target Test Prep
Joined: 09 May 2016
Posts: 161
Location: United States
Followers: 4

Kudos [?]: 117 [1] , given: 0

Re: If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi [#permalink] New post 23 Aug 2018, 16:00
1
This post received
KUDOS
Expert's post
Bunuel wrote:
If 2x − 3y = 6, then 6y − 4x =

A. −12
B. −6
C. 6
D. 12
E. Cannot be determined


Multiplying the given equation by -2, we have:

-4x + 6y = 6y - 4x = -12

Answer: A
_________________

Jeffery Miller
Head of GRE Instruction

GRE Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

Re: If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi   [#permalink] 23 Aug 2018, 16:00
Display posts from previous: Sort by

If 2x − 3y = 6, then 6y − 4x = −12 −6 6 12 Cannot be determi

  Question banks Downloads My Bookmarks Reviews Important topics  


GRE Prep Club Forum Home| About| Terms and Conditions and Privacy Policy| GRE Prep Club Rules| Contact

Powered by phpBB © phpBB Group

Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.